Controle da antracnose e qualidade de mangas (Mangifera indica L.) cv. van dyke, após tratamento hidrotérmico e químico - Carvalho Dias, Mario Sergio; Lima, Luciana Costa [UNESP]; de Castro, Marcos Venicios; Ribeiro Junior, Pedro Martins; Silva, Enilson de Barros (Universidade Federal de Lavras (UFLA), 2005)
Anthracnose causes severe damage to the mango skin. Therefore, there is need to do the post-harvest phytosanitary treatment of the fruits through soaking in fungicide solution, which associated with the hydrothermal treatment has resulted into improved benefits. The present work has aimed at studying anthracnose control and post-harvest quality of mangoes (Mangifera indica L.), cv. Van Dyke after hydrothermal treatment associated with chemical through the physical, physicochemical, chemical and phytopathologic analyses. The mangoes coming from the commercial orchard of the town of Jana ba-MG, of the 2000 crop, were harvested at the commercial maturation stage. After selection according to color uniformity, size and absence of mechanic and physiologic injuries, they were shipped in plastic boxes to the EPAMIG - CTNM - Nova Porteirinha - MG, fruit post-harvest laboratory, where the samples were submitted to the hydrothermal treatment in cold bath in solution containing the fungicides Thiabendazole (Tecto 400 mL/100L), Proclaraz (Sportak 10L/100L) and Imazalil (Magnate 200mL/100L). After air-drying, the fruits were packed in plastic trays and stored at room temperature (25 +/- 2 degrees C and RH 70%) for a 12-day period and evaluated as to the intrinsic quality characteristics every 4 days. The experiment was conducted a completely randomized with 8 treatments, 4 replicates and experimental unit consisting of 4 fruits. The variations of pH, total soluble solids, total titrable acidity and total soluble sugars have not endangered the organoleptic characteristics of mangoes cv. Van Dyke stored under room temperature (25 +/- 2 degrees C and RH 70%) till 8 days' storage. The association of the hydrothermal treatment with the chemical was efficient in fruit anthracnose control for till 12 days' storage. The fungicide Prochloraz (Sportak 110 mL/100L), associated with the hydrothermal treatment, completely inhibited the appearance of anthracnose symptoms.
Anthracnose control and mango quality (Mangifera indica L.) cv. van dyke after hydrothermal and chemical treatment
Keywords: conservation and fungicide